PHYSICOCHEMICAL RHEOLOGY OF FRUIT SYRUP (HONEY) FOR NOUGAT - Marín-Machuca, Olegario (2021)
The rheological properties of different liquid foods and especially of fruit-based syrups depend on different aspects, among which are composition and temperature. One of the most influential aspects is the water content of the syrup and, in general, when the moisture content increases, the viscosity of the fruit syrup decreases. The objective of this work was to determine the physicochemical rheology of the fruit syrup (honey) for the Peruvian nougat "Doña pepa", to obtain the best percentage of synergism of the xanthan and tara gums, and the most suitable formulation for the fruit syrup. Six concentrations of 0.60 %, 0.80 %, 1.00 %, 1.20 %, 1.20 %, 1.40 % and 1.60 % were determined for the two gums. At each of these percentages the apparent viscosity was determined, thus characterizing the flow behavior of the product. The results of pH, soluble solids, and dynamic viscosity of the continuous phase for the temperature concentration (TZ) treatment are shown in tabular form. The most suitable viscosity of the fruit syrup for Doña pepa nougat at different percentages of gums (xanthan and tara) was determined at a temperature of 22°C and a concentration of 84°Brix.  It was concluded that xanthan and tara gums are excellent thickeners for this type of product.